KELUARGA BERENCANA DI KALANGAN KELUARGA PESANTREN DALAM MEMBENTUK KELUARGA SAKINAH (STUDI FENOMENOLOGIS DI PONDOK PESANTREN BAHRUL ULUM TAMBAK BERAS JOMBANG) - Nining Eka Wahyu Hidayati, Umi Sumbulah, (EGALITA, 2009)
This research aims to understand the reason of Pesantren Bahrul Ulum family of Tambak Beras Jombang to participate in family planning program, to decide participating in the program and the implication of the program on establishing harmonious family among the pesantren family.The result of this research reveals thatÂ Â Â  the reason of participating family planning program can be classified into several aspects such as health, psychology, economy, religion and education. Nonetheless, health factor is the most dominant factor. To make decision to participate in the program, the family of the pesantren build intensive two-side communication (so-called â€musyawarahâ€). There are two implications (positive and negative) of famili planning program in relation with establishing harmonious family. One of the positive implication is the understanding that harmonious family may be established if a wife (mother) is not busy with domestic affair due to pregnancy and giving birth many times. As a result, the parents may concern with childrenâ€™s education.Then, for the negative implication is that health problemÂ  affecting to the spouse relationship which tend to be uncomfortable.